Pengembangan Multimedia Flash pada Materi Energi untuk Meningkatkan Motivasi Belajar Siswa - Purnamasari, Riska; Ahzan, Sukainil; Sukroyanti, Baiq Azmi (IKIP Mataram, 2017)
[Title: Development of Flash Multimedia on Energy Materials to Improve Student Learning Motivation]. This study aims to develop flash multimedia on energy materials to improve student learning motivation. This study is a development research with ADDIE model. Flash multimedia validation involves 2 validators (media experts and media design experts). Validation results show on the aspect of the material with a score of 3.6 with the category